PENGARUH KETERAMPILAN BERPIKIR KRITIS SIKLUS BELAJAR 5E BERBASIS STEM PADA MAHASISWA PJKR FKIP UNIVERSITAS PGRI MAHADEWA INDONESIA - I Made Darmada (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
This study aims to analyze the differences in critical thinking skills between students who study with the 5E learning cycle based on STEM and students who learn to use the 5E learning cycle without STEM. Then carried out experimental research by taking the population of this study is the fifth semester students of PJKR FKIP Universitas PGRI Mahadewa Indonesia. The sampling technique used in this research is simple random sampling. This study uses two techniques of analysis of variance. Based on the results of hypothesis testing, it was obtained that there were differences in the effect of the 5E learning cycle based on STEM and the 5E learning cycle without STEM on critical thinking skills.